PERSEPSI PETERNAK TERHADAP KEGIATAN THE DEVELOPMENT OF INTEGRATED FARMING SYSTEM IN UPLAND AREAS (UPLAND) KELOMPOK TANI SEKAR ARUM DESA TUMANGGAL KABUPATEN PURBALINGGA - Kukuh Azani; Supranoto; Fani Evadewi; Susilo Rahardjo (MEDIA PETERNAKAN, 2023)
This study aims to determine the farmer's perception of the activity the development of integrated farming system in upland areas (Upland) Sekar Arum Farmers Group, Tumanggal Village, Purbalingga Regency. Executed on date17 October 2022 to 30 November 2022. The type of research used is descriptive quantitative research, namely research that provides an overview or description of the farmer's perception of activities the development of integrated farming system in upland areas (Upland). The target of this study were members of the Sekar Arum Farmer Group, Tumanggal Village, Pengadegan District, Purbalingga Regency, totaling 30 people. Data collection methods are observation and interviews. The results showed that the farmer's perception of the activity the development of integrated farming system in upland areas (Upland) Sekar Arum Farmer Group, Tumanggal Village, Purbalingga Regency is in the agree category. This can be interpreted that the farmer agrees to the activity the development of integrated farming system in upland areas (Upland) Sekar Arum Farmer Group Tumangal Village Purbalingga Regency. Keywords: Breeders' perceptions, highland integrated agriculture